The Adoption of Open Educational Practices to Support Practical Work at Moroccan Universities - EL Kharki, Khadija; Berrada, Khalid; Bensamka, Faouzi; Burgos, Daniel (Springer Science and Business Media Deutschland GmbH, 2022)
One of the grand challenges of education is to provide free and open access to high-quality educational content, which is addressed by the open educational resources (OER) movement since their first emergence at UNESCO’s 2002 forum. The use of OER is increasingly being recognized as one of the most significant educational movements in the twenty-first century. Indeed, the value and pivotal importance of OER for education have become evident. Nowadays, OER are commonly used, adapted, remixed, and shared. The concept of open educational practices (OEP) refers to practices that include the use of OER in education. Laboratory experiences are a critical part of science education. Given the cancelation of physics practical work from the first-year program of scientific bachelor's degrees in Moroccan universities, universities and instructors have increasingly been expected to offer alternatives to traditional face-to-face laboratories. However, virtual laboratories are an institutional OER initiative and appear to have great potential to provide laboratory experiences in a virtual educational environment, as an alternative to the face-to-face laboratory. In this work, we present the EXPERES project as an OEP aimed to build an OER repository, containing virtual experiments mapped to the physics curriculum for the first year of the bachelor's degree. This chapter presents our experience in adopting OEP, for developing virtual laboratory, then sharing it as OER. The main results of this OER initiative are: (1) the publication of the conceptualization and scripting manual, which is available online under an open access license; (2) the development of a virtual laboratory and its implementation using a Moodle platform to offer open and massive access to the virtual practical activities. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.
Keywords: Cadi Ayyad University; educational platform; EXPERES project; higher education; Moroccan Universities; OEP; OEP adoption; OER; OER mainstreaming; open education; simulations; virtual laboratories; Scopus(2)